2012
DOI: 10.7150/thno.3677
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Reporter Genes and Reporter Probes: Gene and Cell Therapy Applications

Abstract: Positron emission tomography (PET) imaging reporter genes (IRGs) and PET reporter probes (PRPs) are amongst the most valuable tools for gene and cell therapy. PET IRGs/PRPs can be used to non-invasively monitor all aspects of the kinetics of therapeutic transgenes and cells in all types of living mammals. This technology is generalizable and can allow long-term kinetics monitoring. In gene therapy, PET IRGs/PRPs can be used for whole-body imaging of therapeutic transgene expression, monitoring variations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 104 publications
0
88
0
3
Order By: Relevance
“…However, as ACT has demonstrated both profound potency and at times, lethal toxicity, there is a clear need for tracking modalities that can provide additional spatiotemporal information to enable both baseline mapping of T cell localization and real-time visualization of multiple sites of T cell expansion. Quantitative PET imaging is increasingly used for diagnostic purposes and to gauge therapy response in a more accurate and objective manner (42). To our knowledge, this study is the first to utilize PET/CT to conduct highquality, longitudinal whole-body mapping of ACT localization that illustrates how its dynamics affect the course of treatment and survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, as ACT has demonstrated both profound potency and at times, lethal toxicity, there is a clear need for tracking modalities that can provide additional spatiotemporal information to enable both baseline mapping of T cell localization and real-time visualization of multiple sites of T cell expansion. Quantitative PET imaging is increasingly used for diagnostic purposes and to gauge therapy response in a more accurate and objective manner (42). To our knowledge, this study is the first to utilize PET/CT to conduct highquality, longitudinal whole-body mapping of ACT localization that illustrates how its dynamics affect the course of treatment and survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method has inherent limitations, such as radioisotope t 1/2 and cell division in vivo that lead to probe dilution. Reporter gene imaging, whereby cells are transfected with a PET reporter gene that encodes a protein specifically targeted via a radiolabeled reporter probe (7,8), has been used to image adoptive cell transfer of transduced T-cell receptor-engineered lymphocytes (9). Reporter gene imaging allows for longitudinal tracking of cells but relies on the ex vivo transfection of cells and, for clinical translation, the development of nonimmunogenic PET reporter proteins (8).…”
mentioning
confidence: 99%
“…For example, HSV1-tk can be used as a therapeutic gene as well as a reporter gene. Although HSV1-tk has been used extensively in gene therapy clinical trials performed in the United States and Europe (42,43), only 3 clinical HSV1-tk gene imaging studies ( Fig. 1) (36-38) and 1 hNIS gene imaging study (40) have been reported.…”
Section: Gene and Oncoviral Therapy: Clinical Trialsmentioning
confidence: 99%